2021
DOI: 10.1590/s1677-5538.ibju.2020.1092
|View full text |Cite
|
Sign up to set email alerts
|

Trends in urological emergencies in the Era of COVID-19

Abstract: Purpose: To evaluate trends in emergency room (ER) urological conditions during COVID-19 pandemic lockdown. Materials and Methods: Retrospective analyses of renal colic, hematuria, and urinary retention in ER's admissions of a tertiary hospital during the lockdown period (March 19 to May 4, 2020) in Israel. Patient's demographics and clinical characteristics were compared to those in corresponding periods during 2017-2019, with estimated changes in ER arrival and waiting times, utilization of imaging tests, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Overall, our results do not support the evidence provided by Frumer et al 1 that serum PSA levels may increase after administration of a primary cycle of BNT162b2 vaccine. On the contrary, we found that BNT162b2 vaccine may also have a beneficial effect on prostate biology and function, by reducing circulating PSA levels.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Overall, our results do not support the evidence provided by Frumer et al 1 that serum PSA levels may increase after administration of a primary cycle of BNT162b2 vaccine. On the contrary, we found that BNT162b2 vaccine may also have a beneficial effect on prostate biology and function, by reducing circulating PSA levels.…”
Section: Introductioncontrasting
confidence: 99%
“…Serum PSA levels were not significantly different from baseline (median: 0.9 ng/mL; IQR: 0.61-1.88 ng/mL) after the first BNT162b2 dose (median: 0.7 ng/mL; IQR: 0.48-1.26 ng/mL; p=0.074), and were even lower than at baseline after the second BNT162b2 dose (median: 0.7 ng/mL; IQR: 0.39-1.29 ng/mL; p=0.001). Our results suggest that the BNT162b2 vaccine may also have a beneficial effect on prostate biology and function, by reducing circulating PSA levels Frumer et al, 1 have recently reported that serum levels of prostate-specific antigen (PSA) increased significantly from baseline in recipients of 1 and 3 doses of the Coronavirus Disease 2019 (COVID-19) vaccine BNT162b2 (Pfizer-BioNTech, Mainz, Germany).…”
Section: Introductionmentioning
confidence: 65%
“…Lockdown was associated with a reduction of visits to the emergency department for renal colic, haematuria and urinary retention of 37%, decreasing from an average of 451 (2017–2019) to 261 patients (2020) in a study conducted in Israel. The renal colic admission rate also dropped from 19.8% to 8.4% [28]. A similar analysis was conducted in Italy during the lockdown period between March and April 2020, showing a significant reduction in symptomatic ureteral lithiasis admission of 51.2%.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies showed a difference in the number of patients and severity of the condition of patients visiting the ED according to the time of day [26,27]. During COVID-19 period, there was one study showing that more pregnancy patients come to the ED at night-time due to obstetric emergencies [28], and in another study, that the number of urological emergency patients also increased at night-time [29]. Also, because there is no place except ED to receive treatment at night, we predicted that the proportion of patients visiting the EDs in the night-time during the COVID-19 period would increase compared to the pre-COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%